Pengaruh Adversity Quotient terhadap Prestasi Belajar Matematika Siswa - Mayesty, Desintha Paxia; Fatimah, Liya; Sembiring, Andre; Setiawan, Niko; Marhaeni, Nafida Hetty (Educationist: Journal of Educational and Cultural Studies, 2023)
The purpose of this study is to determine the influence of Adversity Quotient on students' mathematics learning achievement. The research was conducted in class VIII of MTs Hidayatussibyan Wadaslintang. The population and sample of the study were all students in that class, so sampling was done using total sampling technique. The instruments used were a questionnaire on the influence of Adversity Quotient and students' mathematics scores on the Periodic Assessment Test (PAT), which met the criteria for validity and reliability. The data analysis used hypothesis testing through simple linear regression analysis. No prerequisite tests were conducted because this study used a valid and reliable questionnaire. The results of the study showed that (1) the Sig. value of 0.000 < 0.05, thus rejecting the null hypothesis (H0), indicating that there is an influence of Adversity Quotient on students' mathematics learning outcomes; (2) the coefficient of determination (R square) was 0.480, indicating that Adversity Quotient accounts for 48% of the variance in students' mathematics learning outcomes, while the remaining 52% is influenced by other variables. The regression equation is Y = -2.375 + 0.822X. It can be concluded that in the absence of Adversity Quotient, students' mathematics learning achievement consistently remains at -2.735. Meanwhile, a 1% increase in Adversity Quotient results in a 0.822 increase in students' mathematics learning outcomes.